O mandado de segurança preventivo e o ato coator iminente na Constituição Federal de 1988 - Macêdo, Potira Ferreira Brito de (2011)
The thesis objective was to study the preventive injunction, in view of the General Theory of Law, in order to organize and deepen their knowledge, especially as regards the possibilities of its filing. It was also to expose what is the understanding of the Brazilian Superior Courts and the Espírito Santo Justice on this matter. There is agreement that the preventive injunction is an constitutional action, which shows his character of a secondary legal norm, which aims to prevent another rule to be issued by the authority constraining. This rule, concrete, constraining party is called constraining act, and requires the commission of other acts in the course of their training process. These acts, concrete rules, were called preparatory acts, against which the filing becomes preventive. Thus, the real and imminent threat, countered by preventive injunction, manifested in acts preparatory. It is from your understanding it becomes possible to assess in what circumstances is applicable to preventive filing. Within this scope, it was concluded that the system of positive law also provides a specific procedure to perform the act of preparation, therefore, for this process, it is a final act. So, the studies lead to the conclusion that the preventive filing, although it aimed at preventing the practice of constraining party act, will always be enforcement of the act preparatory. Thus, the preventive security, in the manner accepted by doctrine and jurisprudence, is a myth.